Psychological Factors Influencing Universal Design for Learning: A Systematic Review on Inclusive Education - Jarar, Syeda Parsa; Kurniawati, Farida (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2025)
This systematic review explores the integration of Universal Design for Learning (UDL) and Self-Determination Theory - Basic Psychological Needs Satisfaction (SDT-BPNS) in early childhood education. By analyzing 14 peer-reviewed articles from 2014 to 2024, this study identifies how UDL practices address relatedness, competence, and autonomy to enhance inclusive education. Findings reveal that collaborative learning environments and positive teacher-student relationships promote relatedness, especially when culturally adapted. Competence is enhanced through scaffolded learning, differentiated instruction, and teacher training programs, though limited resources and inadequate training remain challenges. Autonomy is supported by flexible, creative, and student-centered activities, but institutional constraints often limit its effectiveness. Integrating UDL with SDT-BPNS provides a comprehensive framework addressing both structural and psychological aspects of learning. This approach enhances motivation, engagement, and inclusivity by promoting emotional and cognitive well-being. However, cultural responsiveness, institutional support, and tailored training programs are essential for effective implementation. This review highlights the need for future research to explore long-term effects and develop culturally responsive UDL frameworks that incorporate SDT-BPNS principles.